Humanistic Education in Islam: A Study of Ahmad Syafii Maarif's Thoughts - Amirullah, Amirullah; Arifin, Syamsul; Sari, Zamah (MUADDIB Jurnal Kependidikan dan Keislaman, 2022)
Education in Indonesia, especially Islamic education, has not been sufficient to form a humanist personality and is still primordialistic and sectarian in character. This study aims to show the values of humanistic Islamic education in the thought of Ahmad Syafii Maarifâ€™s. This research is qualitative research with descriptive analysis using library research, and in-depth interviews. This research shows that the essence of education in Ahmad Syafii Maarif's perspective is the process of humanization (a process that liberates and humanizes humans) which directly has an organic link with the spiritual-transcendental dimension.Â In Ahmad Syafii Maarif's thought, it is found that the values of humanistic Islamic education can be summarized in six points, namely: the value of egalitarianism, the value of tolerance, the value of pluralism, the value of justice, the value of universal brotherhood, and the value of peace or non-violence. The results of this study are expected in addition to increasing the wealth of intellectual treasures in the study of the thought of figures in the field of Islamic education, but also can be considered in developing a more humanistic educational foundation and practice.